Effect of Atorvastatin And Garlic on Lipid Profile in Hyperlipidemic Patients - Hussien , Zuhair M; Ahmed , Luma T; Hussain, Qutuba Gh (Diyala Journal of Medicine, 2019)
Background: Hyperlipidemia is one of the most common diseases among Iraqi community, and using herbal medicine in treating hyperlipidemia was a good choice to reduce the side effect of recommended drugs with good results of healing, Garlic (Allium sativum) has been used in herbal medicine for centuries for various health problems. It has a beneficial effect of reducing serum lipids and cardiovascular system disease .The purpose of present study was to evaluate the effects of garlic and atorvastatine on the dyslipidemic people. Aim: The aim of this study is to assist the affectivity of the garlic in lowering the lipid profile in hyperlipidemic patients as well as the effect of time on treatment. Methods: This 12 week, Garlic treated, atorvastatin, Garlic + atorvastatin and non-treated study was conducted on patients with hyperlipidemia (n=40) were divided into 4 groups each comprising 10 patients, first group was control healthy persons, second group was given garlic capsules (500mg) twice daily, third group was given atorvastatin (40mg-Gulf pharmaceutical), fourth group was given both garlic capsules + atorvastatin. Results: After 12 week the garlic + atorvastatin treated group had good results in reduction of total cholesterol (5.23±0.12) triglycerides (1.93±0.12) LDL (1.31±0.14) VLDL (0.87±0.15) as compared with those before treatment. Conclusion: This study suggests that using garlic capsules + atorvastatin in treating dyslipidemia patients are efficiently reduced serum total cholesterol, LDL,VLDL and moderately raised HDL cholesterol as compared with non-treated group ,in addition prolong duration of treatment will assess the benefit effect of garlic + atorvastatin in treatment of dyslipidemia and other cardiovascular system diseases.